A New Index of Currency Mismatch and Systemic Risk - Ranciere, Romain (IMF Working Papers; Working Paper ;, 2010)
This paper constructs a new measure of currency mismatch in the banking sector that controls for bank lending to unhedged borrowers. This measure explicitly takes into account the indirect exchange rate risk that banks undertake when they lend to borrowers that will not be able to repay in the event of a sharp depreciation. Such systemic risk taking is not captured by indicators that are based only on banks' balance sheet data. The new measure is constructed for 10 emerging European economies and for a broader sample that includes 19 additional emerging economies, for the period 1998 - 2008. Comparisons with previous currency mismatch measures that do not adjust for unhedged foreign currency borrowing illustrate the advantages of the new approach. In particular, the new measure flagged the indirect currency mismatch vulnerabilities that were building up in a number of emerging economies before the recent global crisis. Measuring currency mismatch more accurately can help country authorities in their efforts to address vulnerabilities at the right time, avoiding hurting growth prospects.